Design of a mechanism to replicate the wing motion of a hummingbird (2025)
This project aims to develop a prototype of a bio-inspired robot based on the hummingbird's flight mechanism. Although previous designs mimic the flapping motion of this bird, they have yet to fully incorporate the fundamental principles of its flight. The project's objectives are to investigate the hummingbird's flight mechanism, design a mechanical system that replicates its wing movement, build a physical prototype, and evaluate its flight capability. Finally, a quantitative analysis will be conducted based on the obtained results to guide future improvements.